Optimization of foundation design and construction - Andal, Maria Deandra C.
Foundations are a multidisciplinary project and account for roughly 12% of construction costs. As such, the process of foundation design and construction should be continuously improved and optimized. The goal of the study is to integrate foundation design and construction and process optimization. The study sought to optimize the process of foundation design and construction to balance the triangle of competing constraints which consists of quality, cost, and time. The three constraints are not independent of one another. As such, project management techniques were identified to collectively satisfy all three constraints. After conducting self-administered surveys and personal interviews, the resulting optimized project management methodology for foundation design and construction can potentially reduce project cost, reduce project duration, and assure quality in at least 20 ways. Second, the results of the study proved that cost reduction is not limited to the design stage; several opportunities for cost reduction are available from feasibility stage to construction stage. Third, the results of the study showed that project participants typically prioritize project quality. However, time and cost are alternately prioritized by the construction group and the owner. The former prioritizes time, while the latter prioritizes cost. Finally, it was observed that most problems can be avoided through cross-functional cooperation and regular communication, since foundations are a multidisciplinary project. The root cause of a lot of issues can be traced to insufficient planning and communication.